EFEKTIVITAS PAPAN TULIS BRAILLE UNTUK MENINGKATKAN PEMAHAMAN HURUF BRAILLE PADA ANAK TUNANETRA KELAS I DI SLB A KOTA PAYAKUMBUH - Cut Intan Pratiwi (Universitas Negeri Padang, 2015)
Abstract : This research based on the problems which researcher found in the blind children which named SLB A Payakumbuh City. In this school, the children who do not know about braille letters start from a to z letters. It can be seen from the observation that researcher do where children can not demonstrate braille. In this research, the researcher uses experiment method which is pre-experimental design or often named quasi experiment with one group pretest-posttest design type. In this research the observation done twice; they are before experiment and after experiment. The observation which is done before the experiment (01) called pretest, and the observation which is done after experiment (02) called posttest. The pretest is given to the subject of the research to find out the initial condition of the comprehension of Braille letters, after that they given the treatment with Braille board, and the continue by giving posttest to see the result of treatment which has given. The point of pretest and posttest are processed and compare by using mann Whitney test. The result of this research shows that the ability of children comprehension of Braille letters after analyzed by looking at the average result in the pretest is 17,69% meanwhile in the posttest there is an increasing which about 73,84%. The data is processed in order to make it more scientific by using Mann Whitney test. The result are Uhit= 2,5 and Utab= 2 with n=5 in the significant level 95% and α= 0,05. The alternative hypothesis is accepted because Uhit > Utab, so it is proven that braille board is effective to increase the comprehension of braille letters to the blind children. Key words : Pemahaman, huruf braille, papan tulis braille, anak tunanetra